Penguatan Pendididikan Karakter dengan Menggunakan Metode Imtaq dalam Meningkatkan Kualitas Pendidikan di Sekolah Dasar/MI - Suparlan, Suparlan (Lembaga Yasin AlSys, 2021)
Character etymologically comes from the Latin character, which means to make sharp. According to the Big Indonesian Dictionary (2008) character is character, psychological traits, morals or character that distinguishes one person from another. Character can also be interpreted as a habit or habit. In general, character is associated with a distinctive or special trait, or a person's pattern of behavior that distinguishes him from others. Imtaq is the formation of two words, namely, faith and taqwa. Faith comes from the word yu'minu-fahuwa mu'min. According to scholars, the meaning of al-iman means